Kemampuan Representasi Matematis Siswa Dalam Menyelesaikan Masalah Persamaan Garis Lurus Ditinjau Dari Gaya Kognitif Siswa SMP - Onis, Oniansy; Hayati, Laila; Lu'luilmaknun, Ulfa; Turmuzi, Muhammad (Mandalika Mathematics and Educations Journal, 2025)
Abstract Mathematical representation is the ability to express ideas or concepts in visual form (diagrams, graphs, pictures, tables). The cognitive style of students is also related to their mathematical representation, because the cognitive structure of students in remembering problems or processing information obtained during learning will vary. This study is a qualitative descriptive study that aims to describe students' mathematical representation abilities in solving mathematical problems of Field Dependent and Field Independent students. The subjects in this study were students of class VIII-A of SMP Negeri 11 Mataram. The results of this study show significant differences related to mathematical representation abilities in solving linear equation problems between students with FD and FI cognitive styles. FD students cannot solve problems if given problems that are different from the examples taught by the teacher and depend on guidance or direction from the teacher. While FI students can solve problems even though they are different from the examples taught by the teacher because they can use their own thinking without being guided by the method taught by the teacher and do not depend on teacher guidance. Then students with FI cognitive styles are more analytical in solving problems than students with FD cognitive styles. The instruments used in this study were GEFT test sheets, mathematical representation test questions, and validated interview guidelines.